Association of visual and hearing impairments with all-cause mortality in older adults in China - Linxia Zhou; Haiping Huang; Qin Wang; Linlu Peng (BMC Geriatrics)
Abstract Background Few studies have examined the association between visual and hearing impairments with all-cause mortality, with inconsistent findings. Moreover, previous researches often categorized impairments in a simplistic manner without considering severity levels. This study aimed to investigate the association between visual and hearing impairments with all-cause mortality among older adults, focusing on impairment severity, using data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Methods A total of 31,701 older participants were included (median age: 90.0 [IQR: 81.0, 99.0], men: 41.1%). Different levels of visual and hearing impairments were scored and then aggregated and divided into four groups. Cox regression analysis examined the association of visual and hearing impairments with all-cause mortality. Results During a median follow-up period of 3.1 years, a total of 22,555 deaths (71.1%) were recorded. Overall, mortality risk increased significantly with the severity of visual and hearing impairments after adjusting for confounders. Compared to score = 0 group, adjusted HRs for mortality were 1.15 (95% CI: 1.11–1.19, p < 0.001) for score = 1 group, 1.26 (95% CI: 1.21–1.31, p < 0.001) for score = 2 group, and 1.47 (95% CI: 1.40–1.54, p < 0.001) for score ≥ 3 group, respectively. Stratified and sensitivity analysis revealed consistent results. Additionally, the population attributable fraction for visual and hearing impairments with mortality was 10.8%. Conclusions Among older people, all-cause mortality risk significantly increased with the severity of visual and hearing impairments, and the visual and hearing impairments accounted for 10.8% of total deaths. These findings emphasize the importance of vigilant monitoring and management of visual and hearing impairments.